2014
DOI: 10.1063/1.4862781
|View full text |Cite
|
Sign up to set email alerts
|

On the Alfvén wave cut-off in partly ionized collisional plasmas

Abstract: The cut-off of the Alfvén wave, caused by plasma collisions with neutrals in multi-component partially ionized plasmas, is discussed. Full multi-component theory is used, and similarities and differences regarding the classic magnetohydrodynamic theory are presented. It is shown that the cut-off in partially ionized plasma in principle may remain the same as predicted in classic magnetohydrodynamic works, although multi-component theory also yields some essential differences. Due to electric field, the ion mot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 30 publications
2
34
1
1
Order By: Relevance
“…According to Soler et al (2013), the results of Vranjes et al (2008) and Tsap, Stepanov, and Kopylova (2011) agree if we correctly specify the initial conditions. In particular, Tsap, Stepanov, and Kopylova (2011) took the equal initial velocities of ions in contrast to Vranjes et al (2008). Zaqarashvili, Khodachenko, and Soler (2013) suggested that the weak wave flux obtained by Vranjes et al (2008) might be caused by the weak magnetic field strength B adopted in this work.…”
Section: Introductionmentioning
confidence: 49%
See 4 more Smart Citations
“…According to Soler et al (2013), the results of Vranjes et al (2008) and Tsap, Stepanov, and Kopylova (2011) agree if we correctly specify the initial conditions. In particular, Tsap, Stepanov, and Kopylova (2011) took the equal initial velocities of ions in contrast to Vranjes et al (2008). Zaqarashvili, Khodachenko, and Soler (2013) suggested that the weak wave flux obtained by Vranjes et al (2008) might be caused by the weak magnetic field strength B adopted in this work.…”
Section: Introductionmentioning
confidence: 49%
“…However, Soler et al (2013) (see also Vranjes and Kono, 2014) again came to the conclusion, however, that the Alfvén flux may strongly depend on the initial velocity of ions. According to Soler et al (2013), the results of Vranjes et al (2008) and Tsap, Stepanov, and Kopylova (2011) agree if we correctly specify the initial conditions. In particular, Tsap, Stepanov, and Kopylova (2011) took the equal initial velocities of ions in contrast to Vranjes et al (2008).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations